PERHITUNGAN REDAMAN SCINTILASI PADA GELOMBANG RADIO VHF (90 – 108) MHZ MENGGUNAKAN MODEL ITU-R - Nixson J. Meok (Universitas Nusa Cendana, 2012)
Very High Frequency (VHF) working at a frequency 30-300 MHz and can reach large distance if is in a LOS ( Line of Sight). Because of signal transmitter character waving VHF in general LOS, hence waving this susceptible signal is hit by atmosphere damping which in the form of damping because gas, rain, cloud, and scintilation which can cause the happening of induction of dilution of signal. In this research focussed at scintilation damping to know damping happened by doing measurement indirectly, applies model ITU-R by exploiting the data from the Meteorology Klimatology Geophysics or Badan Meterologi Klimatologi Geofisika (BMKG). Result of research indicates that big of scintilation damping to compare straight with frequency amount VHF, that is ever greater assessed from ever greater frequency also happened damping. Then season also influential to damping value where at its the damping value the rains is ever greater compared to dry season.